Short cuts [videorecording (DVD)] - Altman, Robert, 1925-2006; MacDowell, Andie; Davison, Bruce, 1946-; Moore, Julianne; Carver, Raymond, 1938-1988 (Criterion collection, 2004)
While helicopters overhead spray against a Medfly infestation, a group of peoples' lives in Los Angeles intersect, some casually, some to more lasting effect. While they go out to concerts and jazz clubs and even have their pools cleaned, these same folks also lie, drink, and cheat. Death itself seems never to be far away. A look at human life and American culture with over 20 lives interweaving.